2020
DOI: 10.1088/1748-0221/15/02/c02013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of p doping on GaAs/AlGaAs SAM-APDs for X-rays detection

Abstract: Avalanche photodiodes based on GaAs/AlGaAs with separated absorption and multiplication regions (SAM-APDs) will be discussed in terms of capacitance, response to light (gain and noise) and time response. The structures have been fabricated by molecular beam epitaxy introducing a p layer doped with carbon to separate the multiplication and the absorption regions. The thickness of the latter layer defines the detection efficiency and the time resolution of the structure, which in turn allows tailoring the device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…In the past, in-depth studies have been carried out on the behaviours of these devices regarding the doping levels of the various layers, the number of multiplication steps, and the fundamental role of the δ p-doped layer [35][36][37][38]. Thanks to these studies, it was found that a δ p-doping layer of carbon atoms of 2.5 × 10 12 cm −2 is necessary to keep the absorption region unbiased over the whole range of reverse biases, up to the breakdown voltage.…”
Section: Mode Of Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, in-depth studies have been carried out on the behaviours of these devices regarding the doping levels of the various layers, the number of multiplication steps, and the fundamental role of the δ p-doped layer [35][36][37][38]. Thanks to these studies, it was found that a δ p-doping layer of carbon atoms of 2.5 × 10 12 cm −2 is necessary to keep the absorption region unbiased over the whole range of reverse biases, up to the breakdown voltage.…”
Section: Mode Of Operationmentioning
confidence: 99%
“…A possible explanation for this behaviour could be ascribed to small uncontrolled fluctuations of the C atom density in the δ p-doped layer from batch to batch. In this regard, it must be pointed out that we are working in a region where δ p-doped C layers are highly compensated [36], and a small excess of deposited C atoms above the optimal dose might increase defect formation due to atomic pairing [60], consequently decreasing the efficiency of the device.…”
Section: Energy [Ev]mentioning
confidence: 99%
“…As a result, the multiplication process has a higher associated noise, which can significantly degrade the signal-to-noise ratio [5]. Over the years, these devices have seen some significant evolutions to reduce the multiplicative noise via the separation of the "absorption and photon-electron conversion" region from the "multiplication" region (separate absorption-multiplication APDs, SAM-APDs), and the band-gap engineering in the multiplication region [6][7][8].…”
Section: Introductionmentioning
confidence: 99%